2020
DOI: 10.1002/jppr.1586
|View full text |Cite
|
Sign up to set email alerts
|

Role of pharmacists in reducing antibiotic prescribing errors in an emergency department

Abstract: Background Clinical pharmacists and clinically trained pharmacists can detect and correct prescribing errors by reviewing physicians' orders. In addition, prescribing errors related to antibiotics occur frequently in emergency departments (EDs). Aim This study evaluated the role of pharmacists in reducing antibiotic prescribing errors in an ED. Methods One clinically trained pharmacist spent 4 h/day in the ED for 30 days. The pharmacist attended the ward rounds and reviewed medical records to identify prescrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…), the functions of clinical pharmacologists for the rational use of medicines are successfully performed by clinical pharmacists, whose main responsibilities are to check prescriptions and advise medical staff and patients on the use of drugs [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Clinical pharmacists and general pharmacists can detect and correct errors in prescriptions by reviewing medical prescriptions and reduce costs associated with misuse, errors and avoidable adverse events [ 20 , 21 ]. In addition, the implementation at the local level of the practice of analyzing the consumption of antibiotics will allow a comparison of the absolute consumption of antibiotics in the context of a particular medical organization for previous years, and then, using data on absolute consumption, make a relative comparison in accordance with the AWaRe categories.…”
Section: Discussionmentioning
confidence: 99%
“…), the functions of clinical pharmacologists for the rational use of medicines are successfully performed by clinical pharmacists, whose main responsibilities are to check prescriptions and advise medical staff and patients on the use of drugs [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Clinical pharmacists and general pharmacists can detect and correct errors in prescriptions by reviewing medical prescriptions and reduce costs associated with misuse, errors and avoidable adverse events [ 20 , 21 ]. In addition, the implementation at the local level of the practice of analyzing the consumption of antibiotics will allow a comparison of the absolute consumption of antibiotics in the context of a particular medical organization for previous years, and then, using data on absolute consumption, make a relative comparison in accordance with the AWaRe categories.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28] The prevalence of errors in antibiotic prescribing was lower than previously in some studies, which has been related to the number of prescribing medications being low or different settings like hospitals or emergency departments setting which had a higher prevalence of medication errors or the antibiotic policy was poorly implemented. 19,[25][26][27][28]30 In contrast, the percentage of errors was higher than in one study that used electronic prescribing. 29 The study showed that most of the prescribing was for females, related to primary healthcare visiting, which is most suitable for females to visit the center beside their home, and non-significant between pediatrics and adults like previous study.…”
Section: Number Of Antibiotics Per Prescriptionmentioning
confidence: 99%
“…Meta-analysis studies and others explored the high percentage of prescribing errors and emphasized the importance of healthcare centers. [16][17][18][19][20][21][22][23][24] Antibiotic was the most implicated prescribing error at primary healthcare centers. 25,26 Thus, various studies highlighted antibiotic prescribing errors at healthcare facilities.…”
Section: Introductionmentioning
confidence: 99%
“…Another example of relevance for my practice is the work undertaken in Iran examining antibiotic prescribing in an emergency department (ED) . This research examined the impact of having a clinical pharmacist provide a service for the first time to the ED.…”
Section: Conflicts Of Interest Statementmentioning
confidence: 99%
“…Another example of relevance for my practice is the work undertaken in Iran examining antibiotic prescribing in an emergency department (ED). 3 This research examined the impact of having a clinical pharmacist provide a service for the first time to the ED. One could question, how could these findings be relevant and translated to a setting such as Australia, where these roles are well recognised?…”
mentioning
confidence: 99%